2009
DOI: 10.1159/000228317
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Nevus with Pseudomelanomatous Features (Nevus with Regression-Like Fibrosis): Clinical and Dermoscopic Features of a Recently Characterized Histopathologic Entity

Abstract: Background: Sclerosing nevi with pseudomelanomatous features or, else, nevi with regression-like fibrosis (NRLF) are histopathologic simulators of regressing melanoma. Objective: We aimed at evaluating the clinical features in a series of NRLF. Methods: Dermoscopic images of NRLF were re-evaluated according to the amount of regression, the presence of white/blue areas and the 7-point checklist. Results: Forty-six lesions from 44 patients (M:F = 3.4:1; mean age: 42 years) were evaluated. Thirty-seven lesions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
(21 reference statements)
0
25
1
Order By: Relevance
“…Recurrent nevi were originally described as ''pseudomelanoma'' because of the striking histopathologic resemblance of some examples to melanoma. [9][10][11] In recurrent nevi, the regenerated epidermis, with a poorly developed rete pattern and (sometimes) poor adherence to the dermis, may be a major factor in the pathogenesis of this architectural pattern. 12 It seems likely that the presence of single melanocytes associated with a distorted or flattened rete ridge pattern in our cases is also due in large part to the underlying fibrosis and fibrosis-induced changes in melanocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent nevi were originally described as ''pseudomelanoma'' because of the striking histopathologic resemblance of some examples to melanoma. [9][10][11] In recurrent nevi, the regenerated epidermis, with a poorly developed rete pattern and (sometimes) poor adherence to the dermis, may be a major factor in the pathogenesis of this architectural pattern. 12 It seems likely that the presence of single melanocytes associated with a distorted or flattened rete ridge pattern in our cases is also due in large part to the underlying fibrosis and fibrosis-induced changes in melanocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the dermoscopic findings of regression structures and blue-whitish veil remind dermoscopists of malignant melanoma or other malignant skin tumors, while it was reported that nevus with regression-like fibrosis showed regression structures and some coexisted with blue-whitish veil [10]. Regression structures and blue-whitish veil are not always associated with malignant skin tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosing nevi with pseudomelanomatous features or nevi with regression‐like fibrosis present a recently classified entity simulating regressing melanoma induced by minor trauma on pre‐existing nevi . These nevi are typically found on the convex area of the back of young to middle‐aged men .…”
Section: Nevi With Special Featuresmentioning
confidence: 99%
“…A typical trizonal pattern can be observed in histopathology: (i) atypical junctional proliferation and pagetoid spreading; (ii) atypical melanocytic nests within dermal sclerosis; and (iii) residual nevus tissue surrounding and within the cicatricial tissue. In contrast with regressing melanoma, sclerosing nevi with pseudomelanomatous features lack cytological atypia, dermal mitosis, necrosis, tumoral melanosis and nodules of atypical melanocytes . Dermoscopically, sclerosing nevi with pseudomelanomatous features present as atypical pigmented lesions showing often centrally located diffuse gray or white areas covering 10–50% of the lesion's surface (Fig.…”
Section: Nevi With Special Featuresmentioning
confidence: 99%